The Effect of Aerobic and Resistance Training on Gut Microbiome Composition and Its Association with Irisin Protein Levels in Aged Mice: The Role of Faecalibacterium prausnitzii, Clostridium difficile, and Enterococcus faecalis - Esmaeili Sirchi, Maryam; Banaei Borojeni, Jamshid; Mojtahedi, Hossein; Sarrami, Leila (Health Nexus, 2026)
In the aging period, alterations in gut microbiome composition and the decline of myokine proteins—such as irisin—are considered major contributors to metabolic disorders, inflammatory conditions, and muscle weakness. In this context, the role of exercise interventions in simultaneously modulating these two biological indicators has gained increasing attention. The present study aimed to examine the effects of aerobic and resistance training on gut microbiome composition and plasma irisin levels in aged mice, with a focus on three key species: Faecalibacterium prausnitzii, Clostridium difficile, and Enterococcus faecalis. This experimental study was conducted over eight weeks on 40 male Wistar rats assigned to five groups: young control, aged without training, sham, aerobic training, and resistance training. Plasma irisin levels were measured using the ELISA method, and the relative abundance of bacteria was assessed using real-time polymerase chain reaction (qPCR). Data were analyzed using multifactorial ANOVA and Tukey’s post hoc test. The results indicated that aerobic and resistance training led to a significant increase in plasma irisin levels in aged mice compared with the inactive group. Resistance training showed the greatest increase. Additionally, the abundance of F. prausnitzii increased in the trained groups, while the abundance of C. difficile and E. faecalis decreased. Composite microbial health indices (F/BAD, F/Cd, F/Ef) also improved significantly. A positive association between irisin levels and microbial ratios was confirmed. The findings suggest that physical exercise—particularly resistance training—can simultaneously enhance gut microbiome composition and myokine status in the elderly. These results support the central role of the “gut–muscle axis” in the physiological response to exercise and provide a basis for designing personalized training interventions in geriatric medicine.